1989
DOI: 10.1620/tjem.158.269
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of blood pressure to sodium and potassium excretion in Japanese women.

Abstract: The cross-sectional association of blood pressure with urinary sodium and potassium excretion was investigated with a stepwise regression analysis. Spot urine of 7441 females between 40 and 69 years was collected from 169 municipalities (88 urban and 81 rural) covering all prefectures in Japan. The filter paper sampling technique for urine was used to collect samples of subjects from March to December in 1985. Spot urine samples were analyzed for sodium, potassium and creatinine. In addition, 24-hr sodium and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…In the present study, the data on Na, K, Na/Cr, K/Cr and Na/K in urine are cited from previous studies (Takemori et al 1988(Takemori et al , 1989. Subjects and the method of collecting urine sample and the relevant particulars including the season of urine collection and the reasons of limiting the subjects to female were discussed in the previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, the data on Na, K, Na/Cr, K/Cr and Na/K in urine are cited from previous studies (Takemori et al 1988(Takemori et al , 1989. Subjects and the method of collecting urine sample and the relevant particulars including the season of urine collection and the reasons of limiting the subjects to female were discussed in the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The mean sodium intake and blood pressure levels have been found to be correlated in the general population (Gleibermann 1973;Simpson 1985). Some within-population studies on Oriental populations (Kesteloot et al 1980(Kesteloot et al , 1987Takemori et al 1989) ) have indicated that a high intake of salt, pickled vegetables, dried/salted fish, and a low intake of raw vegetables, fresh fruits and citrus fruits are associated with the development of SC. In the study on the taste for salt (Tuyns 1988), among people who systematically added salt to their food, high relative risks for SC, colon cancer and rectal cancer were observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, Oriental populations have lower levels of in take of about 40 mmol/day in men com pared to around 70 mmol/day in Western populations. Referring to the same popula tion in which the independent relationships between sodium and blood pressure have been measured, and including the Intersalt study, the following statements can be made: (1) an independent significant relationship between potassium and blood pressure oc curred less frequently compared to sodium; (2) whenever significant the slope of the re gression relating potassium to blood pres sure was 2-4 times more important than that for sodium [2,3,9]. As potassium lowers blood pressure and sodium increases it, the Na/K ratio often shows the best correlations with blood pressure.…”
Section: Potassiummentioning
confidence: 99%